The state of Indian housewives’ participation in domestic decision making and opposition of domestic violence - Kalita, Mamoni; Tiwari, Aviral Kumar (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
This paper presents the empirical results of a survey of 127 housewives in West Tripura, India in which, quite unlike other surveys conducted by the Indian government, the respondents were specifically asked about their degree of involvement in decision making and opposing domestic violence. It was found that in household decision-making women’s involvement was significantly and positively related to their time spent in the household but there was no significant relationships between the women’s time spent in the household and their raising voice against violence. It was also found that comparatively women in nuclear families were more able to be concerned about their pride and dignity than their counterparts in joint or extended families